Epilepsy research output in Southeast Asian countries: A systematic review - Minh-An, Thuy Le; Sejahtera, Desin Pambudi; Lim, Kheng Seang; Lai, Siew Tim; Tan, Chong Tin (ASEAN Neurological Association, 2019)
Objective: Epilepsy is understudied in Southeast Asian (SEA) countries. This systematic review aimed to determine the number of epilepsy publications performed in SEA and identify factors associated with research output in this region. Methods: Existing academic journal article searches were performed using PubMed, Scopus, Medline and Web of Science till 1st March 2018. Openness is determined by the use of English in medical school and overseas epilepsy fellowship. Results: A total of 702 epilepsy articles have been published in the last 50 years in the SEA region, with an exponential increase of publications after the year 1997, with the cumulative number doubled every 5 years. Only half (54%) were published in the journals with impact factor (IF) ≥1. Majority of the publications (48.2%) employed cross sectional design, followed by animal or laboratory studies (21.1%), with few randomized controlled trials and systematic review/meta-analysis studies (1.7% and 2.3%, respectively). Half (52.9%) of the publications were clinical studies. The number of papers with IF≥1 correlated positively with openness to international standard (R=0.720, p<0.05), and knowledge-based economy (p=0.01). Conclusion: Epilepsy research output in SEA is low in quantity and quality. The output is mainly related to the type of economy (knowledge-based or non-knowledge-based) and openness to international ideas and standard. © 2019, ASEAN Neurological Association. All rights reserved.